Involvement of Peripheral Ionotropic Glutamate Receptors in Orofacial Thermal Hyperalgesia in Rats. Issue 1 (28th September 2011) - Honda, Kuniya; Noma, Noboru; Shinoda, Masamichi; Miyamoto, Makiko; Katagiri, Ayano; Kita, Daiju; Liu, Ming-Gang; Sessle, Barry J; Yasuda, Masafumi; Iwata, Koichi
Background: The purpose of the present study was to elucidate the mechanisms that may underlie the sensitization of trigeminal spinal subnucleus caudalis (Vc) and upper cervical spinal cord (C1-C2) neurons to heat or cold stimulation of the orofacial region following glutamate (Glu) injection. Results: Glu application to the tongue or whisker pad skin caused an enhancement of head-withdrawal reflex and extracellular signal-regulated kinase (ERK) phosphorylation in Vc-C2 neurons. Head-withdrawal reflex and ERK phosphorylation were also enhanced following cold stimulation of the tongue but not whisker pad skin in Glu-injected rats, and the head-withdrawal reflex and ERK phosphorylation were enhanced following heat stimulation of the tongue or whisker pad skin. The enhanced head-withdrawal reflex and ERK phosphorylation after heat stimulation of the tongue or whisker pad skin, and those following cold stimulation of the tongue but not whisker pad skin were suppressed following ionotropic glutamate receptor antagonists administration into the tongue or whisker pad skin. Furthermore, intrathecal administration of MEK1/2 inhibitor PD98059 caused significant suppression of enhanced head-withdrawal reflex in Glu-injected rats, heat head-withdrawal reflex in the rats with Glu injection into the tongue or whisker pad skin and cold head-withdrawal reflex in the rats with Glu injection into the tongue. Conclusions: The present findings suggest that peripheral Glu receptor mechanisms may contribute to cold hyperalgesia in the tongue but not in the facial skin, and also contribute to heat hyperalgesia in the tongue and facial skin, and that the mitogen-activated protein kinase cascade in Vc-C2 neurons may be involved in these Glu-evoked hyperalgesic effects.